Efeitos de elementos centrais e periféricos de avaliações online sobre utilidade percebida e atitudes de consumidores - Pacheco, Joaquim Monteiro Reis (2020)
With the advent of the internet, the development and spread of information technology, word of mouth communication has played a significant role in the online environment. Different factors lead individuals to share their experiences or seek information for some consumption purpose or related personal need. In parallel, another significant phenomenon has been accentuated in recent decades, characterized by the quantification of aspects of everyday behavior. According to the Elaboration Likelihood Model theory, when individuals are faced with some persuasive stimulus, they process the information through two main routes, a central and a peripheral one. The present work, with an experimental approach, aimed to investigate the impact of online consumer reviews stimuli on the perception of utility, attitude and behavior, through three configurations of emphasis on the central and/or peripheral lanes, in the context of health and hospitality services. Three stimuli were developed for both types of companies, configuring a 3x2 factorial experiment. The data collection instrument was developed on the Google Forms platform. Based on the results, it was identified that the central element of the evaluation had the greatest positive effect on the adopted constructs and indicators. The peripheral elements exerted effects that varied from moderate to high, however the set of central and peripheral elements in the stimuli did not result in the greatest effects for several constructs and indicators. Statistically significant differences were also identified between the results for each type of company. Theoretical contributions are offered, and practical implications are proposed.